Entanglements on Orchid Island, Taiwan - Santini, Gabriella (Université d'Ottawa / University of Ottawa, 2021)
Orchid Island, known to its Indigenous residents — the Yami people — as Pongso no Tao, is a beautiful tropical island land located off the southeastern tip of Taiwan. How do the Yami inhabit Orchid Island? With an ocean epistemology in mind, this thesis explores the various forces, materials, and peoples that flow to and from the island, entangling themselves within the Yami’s lifeworlds. From one month of participant observation, engaging with all forms of island life and walking the entirety of the island road, ethnographic vignettes, anecdotes and colourful images are intertwined to form but a glimpse of the Yami people’s story. As the story demonstrates, some Yami are caught in a double bind: knots of tension between conflicting forces entangled through and within the island. There are tensions between members of the community, between humans and non-humans, and between lifeworlds at work. The Yami find various strategies to respond to these double binds. From tension emerges new forms; new ways of being.
Keywords: Taiwan; Yami; Tao; Entanglements; Austronesian lifeworlds; Orchid Island; Indigeniety; Double Bind; Lifeworld